AIDS, Caregiving and Kinship: The Queer “Family” in Bill Sherwood’s Parting Glances - Nikola Stepić (European Journal of American Studies)
As a counterpoint to the emerging homonormativity of the twenty-first century, this paper seeks to identify and reevaluate the potential of queer chosen families as they are cinematically mediated, and historically located, in the context of the AIDS epidemic. With Bill Sherwood’s 1986 film Parting Glances as a case study, the paper argues that the melodramatic mode of these films, with the repetition of tropes such as caregiving, mourning and funerals, ushers an alternative mode of familiality into queer narratives and champions the queer chosen family. In this sense, it is argued that to look at the evolution of queer familial life means to look at a long process of transference of one social modality to another, and the AIDS film specifically as a place where familial relationality is emulated and transformed through relations based in love, friendship and parrhesia.